PERSPEKTIF SOSIOLOGI TENTANG KEPULAUAN - Christine E. Meka; Jim Briand Kolianan; Jeni M. Ataupah (Jurnal Pluralis, 2023)
Islands as a geographical entity have unique characteristics in terms of social interaction, social change and identity construction. In this article, a sociological approach is used to discuss these issues in an island context. Social exchange theory is used to describe social interactions between islands, including economic, cultural, and social exchanges between geographically separated islands. In addition, modernization and social construction theories are used to analyze social change and identity construction in islands, including the influence of globalization, modernization, and local factors in shaping the identity of island communities. In an island context, issues such as migration, mobility, cultural diversity and social resilience become an important focus in a sociological perspective. This article also explores concepts such as third space, geographical imagination, and social identity in understanding social phenomena in the islands. In its conclusion, this article emphasizes the importance of adopting a sociological approach in understanding the complexity of social interactions, social change, and identity construction in islands as a unique geographical entity.